UKRAINE’S SOCIO-ECONOMIC DEVELOPMENT UNDER CONDITIONS OF ECONOMIC CRISIS - Свистунов, Алексей; Войнаренко, Михаил (SWorldJournal, 2020)
Abstract. The peculiarities of Ukraine’s socio-economic development are investigated and their problematic aspects are highlighted in the article, along with their systematic analysis. The need for state regulation increase of transformation processes in